Seems Fair to Me: Dyadic Leader Consensus Mediates Fairness and Group Performance - Berrios-Espinoza, R (SAGE Publications Inc., 2018)
Drawing on both relational and shared leadership theory and utilizing social consensus, we examine the relationship between percieved leader fairness, leader consensus (LC), and group performance. We do so by conceptualizing LC as a new way of hypothesizing and examining shared leadership. LC derives from mutual dyadic perceptions of all members in a team. First, we examine perceptions of leader fairness as a possible antecedent of LC. Second, we investigate the mediational effect of dyadic perceptions of leadership (i.e., LC predicts group performance). In two multisource studies using a round-robin design, we demonstrate that when team members reach a clear consensus about their team leader, perceived leader fairness was positively associated with LC. Furthermore, teams who perceived their leaders as fair exhibited higher group performance. © 2017, © The Author(s) 2017.